Manpower Allocation with Time Windows - LIM, Andrew (Institutional Knowledge at Singapore Management University, 2004)
In this paper, we propose a manpower allocation model with time windows which is of practical interest. This model originates from a real-life port manpower allocation problem where demand is generated from locations in the yard for servicemen who are dispatched from a central point and where the objectives are to minimize the number of servicemen used, travel distances, travel times and waiting times. We develop a tabu-embedded simulated annealing algorithm and a squeaky wheel optimization with local search algorithm for the problem. Experimental results are reported which show the effectiveness of our approaches.